CORRELATION OF CLINICAL SEVERITY AND LABORATORY PARAMETERS WITH DIFFERENT SEROTYPES IN DENGUE VIRUS: A CROSS-SECTIONAL STUDY. - Sunil Kumar; Ravi Kumar; Shashi Kishore; Sanjay Nag (Student's Journal of Health Research Africa, 2024)
Background In tropical and subtropical nations, dengue fever a serious public health concern is brought on by the dengue virus (DENV). Dengue hemorrhagic fever (DHF) and dengue shock syndrome are two examples of the mild to severe forms of the virus. In order to improve knowledge of the variables influencing severe dengue outcomes, the study examines the correlation between clinical severity, laboratory markers, and dengue virus serotypes. Methods The study comprised 130 patients diagnosed with dengue at a tertiary care hospital. Patients were classified into three stages of dengue severity based on WHO guidelines. Serological and molecular diagnostics, including ELISA and RT-PCR, were used to identify DENV serotypes and analyze laboratory parameters. Statistical analyses were performed to evaluate the correlations. Results The participants had average age of 34.5 years, with 55.4% males. Patients were categorized into Stage 1 (43.1%), Stage 2 (36.9%), and Stage 3 (20%) based on severity. Significant differences in laboratory parameters were observed across the stages, with lower platelet counts and higher levels of hematocrit, liver enzymes (AST and ALT), and ferritin in severe dengue cases (p < 0.001). DENV-2 was the most prevalent serotype (35.4%) and was significantly associated with severe dengue (p = 0.025). ROC curve analysis identified ferritin as a potential marker for severe dengue with a cutoff value of 300 ng/mL and an AUC of 0.88. Conclusion The study shows that dengue patients' platelet count, hematocrit, liver enzymes, and ferritin levels are strongly correlated with clinical severity. Serious illness symptoms are associated to DENV-2. These findings emphasise the necessity of serotype identification and laboratory monitoring in dengue management. Recommendations Future studies with bigger sample sizes are recommended to validate these findings. Routine monitoring of ferritin levels and early identification of DENV serotypes could enhance the management and prognosis of dengue patients.